Fingolimod vs dimethyl fumarate in multiple sclerosis: A real-world propensity score-matched study. (10th July 2018) - Prosperini, Luca; Lucchini, Matteo; Haggiag, Shalom; Bellantonio, Paolo; Bianco, Assunta; Buscarinu, Maria Chiara; Buttari, Fabio; Centonze, Diego; Cortese, Antonio; De Giglio, Laura; Fantozzi, Roberta; Ferraro, Elisabetta; et al.
Abstract : Objective: To directly compare fingolimod (FNG) and dimethyl fumarate (DMF) on no evident disease activity (NEDA) status in patients with relapsing-remitting multiple sclerosis (RRMS) from 7 multiple sclerosis outpatient clinics in Central Italy. Methods: We analyzed data of patients with RRMS who started an oral agent, namely DMF or FNG, either as first treatment (naives) or after switching from self-injectable drugs (switchers). We performed a propensity score (PS)–based nearest-neighbor matching within a caliper of 0.05 to select patients with homogeneous baseline characteristics. Pairwise censoring was adopted to adjust for difference in length of follow-up between the 2 treatment groups. Comparisons were then conducted in matched samples with Cox models (stratified by center) with NEDA-3 as the main outcome. NEDA-3 was defined as no relapses, no disability worsening, and no MRI activity. Results: Overall, 483 and 456 patients eligible for analysis started on FNG and DMF, respectively. The PS-matching procedure retained a total of 550 patients (275 per group). After a median on-study follow-up of 18 months, the proportions of patients with NEDA-3 were similar (FNG 73%, DMF 70%; hazard ratio [HR] 0.74, p = 0.078). Subgroup analyses showed a comparable effectiveness of the 2 drugs in naives (n = 170, HR 1.15, p = 0.689), whereas FNG was superior to DMF in the achievement of NEDA-3 status among switchers (n = 380, HR 0.57, p = 0.007). Conclusion: We found no significant difference between FNG and DMF on NEDA-3 status, while subgroup analyses suggest the superiority of FNG over DMF in patients switching from self-injectable drugs. Classification of evidence: This study provides Class IV evidence that for patients with RRMS, DMF and FNG have comparable efficacy in treatment-naive patients and that FNG is superior to DMF in patients switching from self-injectable drugs.